The Inner Line Permit System and governance issues in Manipur - Nair, P.C. (2016)
The Inner Line Permit System (ILPS) that is being followed in Nagaland, Arunachal Pradesh, and Mizoram in the North-East is a matter that was not very well known to most citizens of the country. The issue, however, has come to the forefront with the Meiteis in Manipur today demanding that this system be followed in Manipur as well for the 'demographic inversion' that is taking place in the State, along with the lack of job opportunities to the local youth. The cases of Sikkim and Tripura are often brought to fore to create paranoia amongst the masses. Three bills were passed unanimously by the Manipur State Assembly to implement the ILPS in August 2015. ILPS in the form passed in the bills is widely opposed by the other two demographic sections of Manipur, the tribal Nagas and Kukis, who in these bills see an attempt by the Meiteis to usurp their land and further distance them from development. Besides, there are many other governance issues that the state is faced with.This article discusses what these three bills are and why there is a state of impasse now. It also suggests in what way these bills could be reframed to satisfy all stakeholders, besides also recommending ways by which governance issues can be tackled to ensure economic prosperity and social upliftment in the State. - Reproduced.
Keywords: Inner Line Permit System - India - Manipur; Inner Line Permit System